Algorithmic visibility and the transformation of tour guides’ professional identity in Bali: A conceptual exploration - Agustina, Ni Ketut Wiwiek; Sunarta, I Nyoman; Mananda, I Gusti Putu Bagus Sasrawan; Kristianto, Yohanes (Edelweiss Applied Science and Technology, 2025)
This conceptual paper theorizes how algorithmic visibility reshapes the professional identity of tour guides in Bali. Integrating structuration theory and identity work with platform studies and authenticity research, it develops a framework and propositions rather than reporting empirical data. The framework explains how guides negotiate legitimacy across three regimes—cultural (community norms and ritual propriety), algorithmic (ratings, rankings, engagement), and formal (licensing/associations)—and how tensions among them generate identity strain, emotional labor, and market precarity. We propose that guides respond via identity play, narrative layering, and community anchoring, which differentially affect well-being, service quality, and destination image. The paper contributes theoretically by bridging structure–agency perspectives and reframing authenticity as an algorithmically negotiated practice, and practically by outlining policy and capacity-building levers (e.g., dispute resolution for unfair reviews, greater transparency in ranking, and digital literacy training). Situated within Global South debates on cultural labor and digital mediation, the study delineates a research agenda for ethnography, cross-destination comparison, and quantitative tests of algorithmic effects.